Dinamika Hukum Perkawinan Adat Pada Sistem Kekerabatan Parental/Bilateral Terhadap Masyarakat Sunda - Karwiyah, Karwiyah; Daru Nugroho, Bambang; Kusmayanti, Hazar (Recital Review, 2024)
This paper provides an overview of the legal dynamics and legal sanctions of customary marriage in the parental/bilateral kinship system against the Sundanese community. The approach method applied is in the form of normative juridical or literature law research. The research specifications used are descriptive analytical. Stages of research with literature research that uses primary legal materials, secondary legal materials, and tertiary legal materials. The data collection method is then carried out through literature studies and observations (observations). The method of data analysis is carried out in a qualitative juridical manner. The results showed that customary marriage law in the parental/bilateral kinship system for Sundanese people, including the Sundanese Community in Karawang Regency, applies kinship relations from husband and wife, and so on until their descendants' children later. The marriage is accompanied by a series of traditional marriage ceremony processions from before to after the marriage contract, although some still follow the whole and some adjust. The practice in the Karawang Regency community that a series of marriage customs if there are things that are considered lacking and not in accordance with the customs that should be sanctioned only comes from the surrounding response.